Investigation of Nicotiana tabacum (+) N. suaveolens cybrids with carpelloid stamens - Fitter, John T (Journal of plant physiology, 2005)
To investigate cytoplasmic effects on homeotic floral morphology, Nicotiana tabacum and N. suaveolens protoplasts were fused and cybrids obtained to contrast with the sexual alloplasmic line Nta(sua)S. Nta(sua)S contains the nucleus of N. tabacum and cytoplasm of N. suaveolens while cybrids derive from fused cells where the cytoplasms can interact. The three male-sterile somatic cybrid plants analyzed contained mitochondria with N. tabacum and N. suaveolens mtDNA sequences, but not all the N. tabacum or all the N. suaveolens mtDNA sequences were present. The flowers were N. tabacum-like but with a split corolla (not observed in Nta(sua)S) and the whorl of stamens replaced by a whorl of carpel-like structures. Based on scanning electron microscopy the carpelloid stamens had a characteristic N. tabacum stigma, a style of variable length and a pseudo-ovary with ovule-like structures. The Southern blot data were consistent with mtDNA recombination. These genomic changes were maternally inherited. Chloroplasts were either of the N. tabacum or N. suaveolens type. AFLP analysis showed transfer of variable amounts of N. suaveolens nuclear DNA. However, it is the presence of the N. suaveolens sequences and/or absence of N. tabacum sequences in the mitochondria that correlates with the homeotic floral morphology. These cybrids will facilitate the analysis of the role of mitochondrial DNA sequences in floral organ identity; which has received limited attention in genetic flowering models based primarily on Arabidopsis research